Elevated Blood Pressure in the Acute Phase of Stroke and the Role of Angiotensin Receptor Blockers. (31st January 2013) - Lattanzi, Simona; Silvestrini, Mauro; Provinciali, Leandro
Abstract : Raised blood pressure (BP) is common after stroke but its causes, effects, and management still remain uncertain. We performed a systematic review of randomized controlled trials that investigated the effects of the angiotensin receptor blockers (ARBs) administered in the acute phase (≤72 hours) of stroke on death and dependency. Trials were identified from searching three electronic databases (Medline, Cochrane Library and Web of Science Database). Three trials involving 3728 patients were included. Significant difference in BP values between treatment and placebo was found in two studies. No effect of the treatment was seen on dependency, death and vascular events at one, three or six months; the cumulative mortality and the number of vascular events at 12 months differed significantly in favour of treatment in one small trial which stopped prematurely. Evidence raises doubts over the hypothesis of a specific effect of ARBs on short- and medium-term outcomes of stroke. It is not possible to rule out that different drugs might have different effects. Further trials are desirable to clarify whether current findings are generalizable or there are subgroups of patients or different approaches to BP management for which a treatment benefit can be obtained.